Local content in local voices - Grimshaw, David J.; Ara, Rocio (Technical Centre for Agricultural and Rural Cooperation, 2007)
New technology is becoming more accessible to rural communities in the Cajamarca region of Peru in this podcasting experiment. Farmers can now get relevant information in a language they can understand.